2002
DOI: 10.1007/s004040100214
|View full text |Cite
|
Sign up to set email alerts
|

The effect of methyldopa treatment on uterine, umblical and fetal middle cerebral artery blood flows in preeclamptic patients

Abstract: The purpose of this study was to evaluate the efficacy of methyldopa in the treatment of preeclamptic patients. This study was performed on 24 preeclamptic women who were in between 25-36 weeks of gestational age. 24 healthy pregnant women were taken as control group. Before starting treatment, 24 preeclamptic patients were examined with Doppler ultrasound. Pulsatility index, resistance index, systolic/diastolic ratio of uterine, umblical and fetal middle cerebral arteries were measured. Preeclamptic patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 6 publications
1
6
0
7
Order By: Relevance
“…Our data confirm the findings of previous studies indicating that, before antihypertensive therapy, uterine artery PI and RI are increased in women with pre‐eclampsia but not in women with gestational hypertension, compared to normotensive controls23, 28–32. The impairment of uteroplacental perfusion found in pre‐eclampsia can explain the less favorable fetal and neonatal outcomes observed in these cases compared with pregnancies complicated by gestational hypertension33–35.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our data confirm the findings of previous studies indicating that, before antihypertensive therapy, uterine artery PI and RI are increased in women with pre‐eclampsia but not in women with gestational hypertension, compared to normotensive controls23, 28–32. The impairment of uteroplacental perfusion found in pre‐eclampsia can explain the less favorable fetal and neonatal outcomes observed in these cases compared with pregnancies complicated by gestational hypertension33–35.…”
Section: Discussionsupporting
confidence: 91%
“…We found that, independent of gestational age, α‐methyldopa therapy had no significant effect on uterine artery Doppler resistance to blood flow in 51 cases of pre‐eclampsia and 29 cases of gestational hypertension. Four smaller studies that previously examined the effect of α‐methyldopa on uterine artery Doppler indices in women with hypertensive disorders of pregnancy yielded conflicting results23–26. The first study by Montan et al 24 included 20 women presenting with pre‐eclampsia in the third trimester.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study done by Günenç et al, treatment with methyldopa lowered the uterine artery resistance in preeclamptic patients but did not affect the resistance of umbilical and fetal middle cerebral artery [9]. In two separate studies done by Khalil et al and Muračević et al, they did not find change in flow resistance of umbilical artery after administration of methyldopa [10, 11].…”
Section: Discussionmentioning
confidence: 99%